Organic certification, agro-ecological practices and return on investment: Farm level evidence from Ghana - Linda Kleemann; Awudu Abdulai (Kiel Institute for the World Economy (IfW), 2012)
The recent empirical literature on economic sustainability of certified export crops shows that certification standards that enhance yields are important for improving farm revenues and farmer welfare. However, limited evidence exists on the impact of organic certification on the adoption of agro-ecological practices. In this study, we use unique farm-level data from Ghana to examine the impact of organic certification on the use of agro-ecological practices to improve environmental conditions, as well as how using these measures affect farm outcomes such as return on investment. In the former, we utilize an endogenous switching regression approach to account for selection bias due to unobservable factors. Our empirical results reveal that organic certification increases agro-ecological practice use, although from a very low starting point. Using a generalized propensity score approach, we show that there is a nonlinear relationship between the intensity of agro-ecological practice use and return on investment.
Keywords: O13; Q13; Q17; Q56; 330; organic agriculture; certification; agro-ecological practices; return on investment; impact assessment